Education Quality Assurance: The Controversy Between Quantity and Quality - Happyana, Lu’at; Khaudli, Muh. Imam (SAINTIS Publishing, 2025)
This research analyzes the challenges of ensuring educational quality with a focus on the balance between quantity and quality in secondary education at MA YPI Darul Huda Lubuk Harjo, Palembang. Using a qualitative approach with case study methods, this research explores limited resources, community demands for quantitative results, and weaknesses in monitoring and evaluation. Data was collected through in-depth interviews, participatory observation, and analysis of documents related to quality assurance policies and implementation. The research results show that limited funding and infrastructure affect the quality of educational services, while society's demands are often oriented towards measurable results, such as graduation rates and test scores, ignoring the holistic learning process. In addition, monitoring and evaluation processes that tend to be administrative without in-depth reflection weaken the effectiveness of quality assurance. This research recommends increasing resource support, public education, and developing a more comprehensive monitoring system to achieve a balance between quantity and quality in education quality assurance.